'Not the same person anymore': groupwork, identity and social learning online. Issue 2 (4th May 2017) - Jaber, Rowaida; Kennedy, Eileen
Abstract: This paper argues that identity may be key to understanding why social presence has been considered so important to successful learning experiences. A qualitative case study of 10 students and 4 tutors in an online postgraduate education program was conducted. The research applied the work of Goffman to explain the relationship between social presence and support for the social production of identity online. Semi-structured individual and group interviews revealed the importance of trustworthy social interaction to support students' performance of identity and identity shifts in fostering deeper social learning. Implications for the design of effective online learning experiences are provided.